1991
DOI: 10.1159/000125705
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Delta Sleep Inducing Peptide and Luteinizing Hormone Releasing Hormone in Neurosecretory Vesicles in Rat Median Eminence

Abstract: The colocalization of immunoreactivities similar to delta sleep inducing peptide (DSIP) and luteinizing hormone releasing hormone (LH-RH) was investigated by light and electron microscopic immunocytochemistry in the rat median eminence. At the light microspic level, DSIP and LH-RH immunostained fibers, and varicosities exhibited a similar distribution pattern throughout the median eminence. Immunoreactive axons were mainly found in the lateral part of the external layer. Using an elution-restaining technique, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Virtually all LGVs were multiple/ dually labeled in both central and peripheral projections, whereas double (multiple)-labeled LGVs were relatively rare in the cell body. Although the central and peripheral projections of individual DRG neurons could not be followed, these observations showed that: (1) a mixture of neuropeptides was packed within individual LGVs, i.e., when multiple peptides were produced by one neuron, they were not selectively packaged in different LGV subpopu- Vallet et al 1991 lations; (2) LGVs (and therefore the neuropeptides packed therein) were found at both central and peripheral projections of the DRG neurons. If these points can be generalized, there is presumably no selective transport to functionally different neuronal processes (the axons and the dendrites) and/or to different branches of the same process.…”
Section: Subcellular Segregation Of Neuropeptides and Low-molecular-wmentioning
confidence: 99%
“…Virtually all LGVs were multiple/ dually labeled in both central and peripheral projections, whereas double (multiple)-labeled LGVs were relatively rare in the cell body. Although the central and peripheral projections of individual DRG neurons could not be followed, these observations showed that: (1) a mixture of neuropeptides was packed within individual LGVs, i.e., when multiple peptides were produced by one neuron, they were not selectively packaged in different LGV subpopu- Vallet et al 1991 lations; (2) LGVs (and therefore the neuropeptides packed therein) were found at both central and peripheral projections of the DRG neurons. If these points can be generalized, there is presumably no selective transport to functionally different neuronal processes (the axons and the dendrites) and/or to different branches of the same process.…”
Section: Subcellular Segregation Of Neuropeptides and Low-molecular-wmentioning
confidence: 99%
“…To date, three neuroactive compounds have been reported to colocalize in GnRH neurons: (1) a [3-endorphin-like endogenous opioid (Leonardelli and Tramu, 1979;Beauvillain et al, 1981), (2) galanin (Coen et al, 1990;Merchenthaler et aL, 1990), and (3), g-sleep-inducing peptide (Chamay et al, 1989;Vallet et al, 1991). Colocalized galanin exhibits a sexually dimorphic distribution, varies during the estrous cycle, and may enhance GnRH release at the ME terminals (Marks et al, 1993(Marks et al, , 1994.…”
Section: Synaptic Input and Neurotransmitter Colocalizationmentioning
confidence: 99%
“…Intensive investigation of this substance undertaken later by different research teams revealed that DSIP or some other peptide(s) similar in structure is present, free or bound, in the peripheral organs, tissues, and fluids of the body, as well as in the pituitary, hypothalamus, and limbic system of the brain, where it is localized together with a number of peptide and nonpeptide transmitters [2,6,8,14]. There are data on the participation of this peptide in quite a number of normal and abnormal reactions (stress, immune, pain, endocrine), as well as in the regulation of the circadian rhythms, the formation of alcohol and opioid dependence, etc.…”
Section: Abstract: Dsip Peptide; Sleep; Ratsmentioning
confidence: 99%